A Sociological Study of the Impact of Capital Types on the Tendency to Commit Crime (Case Study: Young People Aged 18-29 in Ahvaz) - Ali Hossein Hossein Zadeh; ali boudaghi; Emel Khamisi (توسعه اجتماعی, 2021)
In the present age, one of the issues that have attracted the attention of thinkers and Social science experts; is tendency to commit crime among young people. Basically, the growth and development of crime inclination among youths threatens the legitimate opportunities of societies to achieve cultural aims, which in turn erodes the components of economic, social and cultural development. Accordingly, the main goal of this research is to do a sociological study of the impact of different types of capital on the tendency to commit crime mong Young People Aged 18-29 in Ahvaz the method used is survey and 262313 people in 2020, of which 383 people were selected as a sample based on Cochrans formula. In the present study, the muliti-stage cluster sampling method is used and the data collection instrument is a questionnaire. The results represents that the inclinatition to commit crime among the youths of ahwaz (60/74) is lower than the average. Also, the findings of the present study represents that there is a significant relationship between the variables of cultural capital, economic capital, social capital and the inclination to commit crime. The results of regression analysis represented that the variables included in the model, namely economic, social and cultural capital, explain 0/35 of the variance of the Tendency to commit a crime. Compared to other variables included in the model, cultural capital with beta coefficient (-0.48) had the greatest impact on the research problem